Analisis tata kelola BUMDes Sahabat Kita dalam meningkatkan pendapatan asli Desa Solo - Oktavianey Radha; Andreas Rengga; Thadeus Fransesco Quelmo Patty; Elisabeth Yessi Da Rato (Journal of Economics Research and Policy Studies, 2025)
This study aims to analyze the governance of the Sahabat Kita Village-Owned Enterprise (BUMDes) as an instrument to increase the Village Original Revenue (PADes) in Solo Village, Nagekeo Regency. This study employs a qualitative approach, using data collection methods including in-depth interviews, observation, and documentation. The study involves the village head, BUMDes management, and village community members as informants. The data analysis technique employed is interactive analysis, as described by Miles and Huberman, which involves four stages: data collection, data reduction, data presentation, and conclusion. The research results indicate that, although the Village-Owned Enterprise (BUMDes) has managed five business units, weaknesses remain in planning, policies, and financial transparency, which hinder the optimization of village revenue. Several key success indicators, including promotions and sales of goods through social media, have improved; however, the main challenges lie in managerial aspects and regulatory compliance, which have not been fully achieved. These findings provide recommendations for village governments to strengthen their organizational capacity and improve transparency in managing BUMDes, thereby supporting increased Village Original Revenue.